ANALISIS FAKTOR-FAKTOR PENYEBAB TERJADINYA KREDIT MACET PADA KUD RAHMAT WIDODO KECAMATAN SRUWENG KABUPATEN KEBUMEN - Wahyuningsih, Sri; Fatonah, Ari (ANALISIS FAKTOR-FAKTOR PENYEBAB TERJADINYA KREDIT MACET PADA KUD RAHMAT WIDODO KECAMATAN SRUWENG KABUPATEN KEBUMEN, 2017)
This research aims to analyze what are the factors that can cause bad debt to KUDRahmat Widodo, Sruweng, Kebumen. Independent variables used in this study include Character (X Conditions (X1), Capacity (X2), Capital (X 3), Collateral (X 4), 5). While the independent variable used is the Bad Debt (Y). The  methods  of  data  collection  was  conducted  throught  questionnaires, interviews, and with the way the study of literature relating to the subject matter. Data measurement techniques using Guttman Scale, the value is 1 for yes and 0 for no answer. Research methods used are Regression Analysis by using SPSS version 16. Hypothesis testing using t-test and F test.  Research object in this study is USP KUD Rahmat Widodo and the number of respondents is 51 debtor. The results showed that the Capacity and Condition variables significantly influence their bad debt. Collateral and Character variables are not significant influence on bad debt. While the Capital variable does not influence the existence of bad debt. The  advice  given  on  this  study  (1)  for  the  KUD  Rahmat  Widodo  in determining a credit analysis to members should acctually performing checks on prospective debtor, such as 5 C to analyze factors especially factor Capacity and Condition debtor becomes more dominant cause of the bad debt. (2) for futher research that examines the same issue that adds to other variables that research result more accurate. (3) for the public in using loans in accordance with the requirements which have been planned to avoid bad debt.